Five-Finger Relaxation Technique on Fatigue and Pain of Breast Cancer Patients - Dew, Rosliana; Rahayuwat, Laili; Kurniawan, Titis (International Journal of Psychosocial Rehabilitation, 2020)
Fatigue, and pain are symptoms most often found on breast cancer patients. To overcome them, the five-finger relaxation technique is considered effective. This research aims at identifying its effects on fatigue and pain of breast cancer patients. The method of this research applies the quasi-experiment. The population comprises breast cancer patients benefiting from healthcare services at Hospital. The sampling was done by consecutive sampling-both the control and the intervention groups have 30 members. The intervention group received the standard therapy from the hospital and a 15-session five-finger relaxation technique for 10-15 minutes, every other day, for the duration of a month. The measurement tools were FACIT, and BPI. The analysis used Paired Sample t-Test and t-Independent Test. The result of the research shows a difference in scores of pre-test and post-test fatigue and pain in both control and intervention group due to p value < 0.05. There is a score difference in the two symptoms between control and intervention group, with the former having lower scores than the latter. This research concludes that there are effects of five-finger relaxation technique on the fatigue, and pain of breast cancer patients.